Advances in visual informatics : 6th International Visual Informatics Conference, IVIC 2019, Bangi, Malaysia, November 19-21, 2019, Proceedings /: 6th International Visual Informatics Conference, IVIC 2019, Bangi, Malaysia, November 19-21, 2019, Proceedings. (2019) - Unknown
No abstract available